Traxler, Franz; Huemer, Gerhard (2007). Handbook of Business Interest Associations, Firms Size and Governance - Martín Artiles, Antonio (Papers. Revista de Sociologia, 2007)
Reseña de la obra de Franz Traxler y Gerhard Huemer aparecida en 2007, Handbook of Business Interest Associations, Firms Size and Governance. Oxon: Routledge. 442 p. ISBN10: 0-415-42466-6